Efektivitas Hukum terhadap Perlindungan Korban Kekerasan Berbasis Gender dan Anak di Kabupaten Banyumas: Studi di Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak - Putri, Septiani Aditiya; Anggraeniko, Litya Surisdani; Aji, Alan Bayu (LPPM Universitas Harapan Bangsa, 2023)
Gender and child-based violence in Banyumas is relatively high. This is indicated by the case data of the last 2 years released by the UPTD PPA Banyuma. This study aims to determine the effectiveness of laws and efforts to protect victims of gender-based violence and children, as well as the obstacles faced by UPTD PPA. This study uses empirical research methods, data collected by interviews, observations, and literature studies. The results of this study indicate that the effectiveness of the law on the protection of victims of gender-based violence and children in Banyumas has been effective, it is measured from 5 factors, namely legal factors, law enforcement officers, facilities or facilities, society and culture, where society and cultural factors are also obstacles for UPTD PPA. Efforts to protect victims of gender-based violence and children by UPTD PPA Banyumas conducted in 2 (two) ways, namely preventive and repressive efforts.